Two new diploid species of Isoetes (Isoetaceae: Lycopodiopsida) from Southeastern China based on morphological and molecular evidence - Liu, Chenlai; Yu, Xiaolei; Song, Xiaoli; Shao, Jingjing; Chen, Yuchu; Liu, Xing (Phytotaxa, 2024)
Two new endemic Isoetes from Zhejiang, China, Isoetes changleensis (2n = 22) and Isoetes yuhangensis (2n = 22), are described and illustrated. The morphological characteristics of I. changleensis, such as the presence of tuberculate and irregularly rugulate megaspores having a broad equatorial band with densely rugulate ornamentation, make it easy to distinguish it from Isoetes longpingii. Isoetes yuhangensis has rugulate megaspores with fibrous perispores, which sets it apart from closely related species. To distinguish the new Isoetes species and explore their phylogenetic position, this study employed complete nuclear genomes and plastomes. Both proposed species obtained high support in the phylogenetic analysis as new species. On the basis of morphological traits, chromosome information, and molecular evidence from chloroplast and nuclear DNA, these two taxa are regarded as two new diploid species of Isoetes.